LEARNING FROM TRADITIONAL KNOWLEDGE SYSTEMS TO ENRICH DEVELOPMENT: WORLD BANK EXPERIENCE - Gorjestani, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
This lecture will argue that traditional knowledge systems embedded in impoverished communities represent the intellectual capital of the poor. This intellectual capital is a significant resource which could help enrich the development process and contribute to achieving the Millennium Development Goals. For example, in the health area, traditional medicine approaches can help to provide affordable and generally effective health care for more people, especially the poor. The lecture will then explore the lessons of experience of the World Bank’s Indigenous Knowledge for the Development Program and the challenges in moving forward and in raising awareness about the important role that traditional knowledge systems can play in the development process. One of these challenges is to change the prevailing mindsets among development practitioners regarding the utilization of the traditional knowledge base of the poor in the development process. Another is to develop approaches to validation of indigenous knowledge that are adapted to the specific nature of such knowledge systems. Finally, there is a need to develop innovative approaches for the protection of community-based knowledge systems.